Chapter 1: Collapse, cataclysm, and eruption: Alien archaeologies for the Anthropocene - Rich, Sara A.; Campbell, Peter B. (Sidestone Press Academics, 2023)
Our shared planet is becoming increasingly alien in the Anthropocene, and increasingly inundated. These radical changes to our home call for critical considerations of collapse – when destruction comes from above and rains downward – and cataclysm – as in flood or deluge, when destruction surges up from below – alongside eruption – or hyperbolic destruction spewing forth from a container as small as a split atom. The authors propose that a theoretical framework of object orientation offers a way for archaeologists, especially those whose work brings them into the sea, to contribute more meaningfully to contemporary research about our planet’s pastpresent- future. We have two primary aims: 1) to help usher the alienated subdiscipline of maritime archaeology into the broader discourse of the humanities; and 2) to issue a call to action for fellow maritime archaeologists to respond to ecocide more urgently, more crossdisciplinarily, and more responsibly with new interventions into old research questions. After defending the unique relevance of object orientation to the humanities and social sciences – archaeology specifically and maritime or nautical archaeology most of all – it will pose some relevant questions on how to use our research expertise to move forward, while establishing effective methodologies for thinking and communicating the nonhuman to students and the general public. Ultimately, this paper advocates for mobilizing a radical shift in how humans think and care for all the objects sharing our lives, and our destinies, which are increasingly impacted from above, below, and within.
Keywords: Apocalypse; Anthropocene; archaeological theory; maritime studies; nautical archaeology; new materialism; object-oriented ontology